Manajemen Kompetensi Sosial Guru Sejarah Kebudayaan Islam di Madrasah Aliyah Al-Ikhsan Beji Kedungbanteng - Nurfuadi Nurfuadi (Journal on Education, 2023)
The main goal of education is to create the next generation who are intelligent and have a cultured national character. Despite facing formidable challenges, education is a shared responsibility that involves all elements of society, not just teachers. In the context of a pandemic, there is a silver lining in encouraging a movement so that everyone can become teachers for children, so that the education process continues despite facing various obstacles. In this case, it is important to choose the best people who can be involved in teaching and guiding children (Oktavia et al, 2021). In the context of developing the quality of learning at Madrasah Aliyah Al-Ikhsan Beji Kedungbanteng, competency management for Islamic Religion education teachers plays an important role. The steps taken in planning teacher competency management include several things. First, teachers make syllabus, lesson plans, Prota, and Promissory notes as a guide in planning lessons. In addition, they also use a question bank that contains various types of exams to test students' understanding. Teachers also utilize subject books from the Ministry of Religion and triad publishers, and create book modules based on the results of subject teacher deliberations. In addition, teachers also actively participate in Subject Teacher Consultations with State Madrasah Aliyah in Banyumas district, as well as participate in training to improve competence in implementing the curriculum. By carrying out these steps, it is expected that the quality of learning in the madrasah can continue to develop and have a positive impact on student development. In conclusion, learning in Islamic cultural history material, students are given the task of studying the next sub-chapter by using Student Worksheets (LKS) and book packages. While waiting for their turn, students can study independently by studying questions on LKS and book packages. Furthermore, students who have finished or have not been called for oral exams are still directed to continue studying by using book packages and worksheets. Thus, students can study independently and continue to improve their understanding of Islamic cultural history material.